ABOUT THE INTEGRATION OF EDUCATIONAL SUBJECTS IN THE SYSTEM OF HIGHER PROFESSIONAL EDUCATION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The paper deals with the integration of academic subjects in the system of higher professional education.